Big Data and Audit Quality: Theoretical Study - Hima, Zakaria; Yusoff, Wan Sallha; Saraih, Ummi Naiemah binti (South Asian Journal of Social Sciences and Humanities, 2024)
This paper provides an extensive examination of academic research focusing on the application of big data in relation to audit quality. The literature review is derived from published articles in auditing-related journals. Our review is structured around three primary impacts of applying big data in accounting, auditing, and audit quality. Within each effect, we delve into the findings pertaining to the quality of audits and financial reports. We assert that the limited empirical evidence, coupled with recent technological advancements in information technology, creates opportunities for future research to explore the significant effects of big data application on audit quality and auditing in a broader context.